On Sat, 10 Jul 2010, Zbigniew Komarnicki wrote:
< > Is there any possibility to tell maxima to simplify above eq1 to this form
< > e(r+1, k+1) - e(r, k+1) = C . ( x(r, k+1) - x(r+1, k+1) )
<
< I'm very sorry, the above should simplify to:
< e(r+1, k) - e(r, k) = C . ( x(r, k) - x(r+1, k) )
<
eq : e(r+1, k+1) - e(r, k+1) = C . ( x(r, k+1) - x(r+1, k+1) );
subst(k=k-1, eq);
will do what you want. Perhaps you have a more sophisticated example
in mind?
Leo
--
The University of Edinburgh is a charitable body, registered in
Scotland, with registration number SC005336.